The effect of liming, sowing methods and behaviour of winter forage species upon the natural pasture improvement - Oliveira, Odoni Loris Pereira de; Barreto, Ismar Leal (Pesquisa Agropecuaria Brasileira, 2014)
Annual ryegrass, fescue and phalaris in mixed with white clover and birds foot trefoil were introduced into natural pastures by broadcasting or sowing in rows under the application of 0, 1, 2 and 4 ton/ha of lime. The experiment was conducted in Guaíba, Rio Grande do Sul, Brazil. The soil was a Latosol of the São Jerônimo serial. Values of dry matter production, botanic composition, production and percentage of crude protein were determined in the second year after planting. pH values in the superficial layer (0-10 cm) increased with lime application. Dry matter and protein increased linearly when lime was increased from 0 to 4 ton levels. Annual ryegrass decreased with liming. White clover was the predominant species, representing 60% of the total dry matter produced when 2 and 4 tons were applied. At lower liming levels birds foot trefoil produced about 20% of the total dry matter. Natural vegetation represented from 35 to 45% of the total when the liming levels were 0 and 1 ton/ha, but at higher levels the production was not significant. Weeds almost disappeared with the increase of lime. The average percentage of crude protein was greater than 15% in all treatments being higher at 2 and 4 ton levels. These values are much higher than those obtained from natural pastures.